Electoral Geography as a New Mean of Analyzing Social Change. Kraków City and Małopolskie Voivodship Case Study - Haydukiewicz, Lech (Bulletin of Geography. Socio-economic Series, 2011)
The paper describes political support for Polish political parties as aggregated into four principal options (left-wing, liberal, populist, and right-wing) as well as flux in the electorate in Małopolskie voivodship in the last two decades in order to show regions of electoral stability that tend to do favour the four principal social and political options. Stabilization of cultural and political identity and gradual changes therein are shown by comparing dominant political options with selected social and economic data. The comparison should also allow for a reasonable prediction of future gains and losses for each political option.